Kloning dan karakterisasi daerah promoter gen penyandi ADP glucose pyrophosphorylase dari Metroxylon sagu rendemen pati-tinggi dan -rendah [Cloning and characterization of promoter region of ADP glucose pyrophosphorylase-encoding gene from Metroxylon sagu with high- and low-starch content] - Asmini BUDIANI; Riza Arief PUTRANTO; Hayati MINARSIH; Imron RIYADI; . SUMARYONO; Barahima ABBAS (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2016)
ADP-glucose pyrophosphorylase (AGPase) is one of the key enzymes in the starch biosynthesis. In many plants, the activity of this enzyme was reported to affect the yield and composition of the produced starch. This research is a part of an effort to develop molecular markers for early selection of high starch-yielding of sago palm. The purpose of the research was to isolate promoters of AGP gene and to analyze the differences in their DNA sequences between sago palm with high starch content (MsHS) and low starch content (MsLS). DNA was isolated and purified from the leaves of the two sago palm. The promoter region of AGP was amplified by Genome Walking technique. The specific primers were designed by Primer3 program based on the information of DNA sequence of AGP genes of sago palm from previous studies. Selected DNA fragments resulted from Genome Walking were isolated from the gel, cloned into E. coli, and analyzed its DNA sequence. DNA sequence analysis showed that one DNA fragment from MsHS (± 1500 bp) and one DNA fragment from MsLS (> 2000 bp) were confirmed as a 5’ upstream of the AGP gene. Further in silico analysis using MEME program identified various DNA motifs of cis-acting elements, which confirmed that those DNA fragment were promoter region of the gene. Preliminary analysis showed the differences in DNA sequences and motives of cis-acting elements in the promoter region of the two samples which might influence or indirectly associated with the character of the starch yield in sago palm.